MELAYUNYA ETIKA BISNIS DALAM MASYARAKAT ISLAM MELAYU NUSANTARA - Taufik Akhyar (Wardah, 2015)
Islamic Society Malay archipelago has been known as the people who always uphold the ethics and morals in a variety of activities, but along with the development and progress , especially in science and technology and the impact of globalization and materialist culture is slowly these conditions increasingly withered and show weakness . It can be seen from the various cases of irregularities business ethics and akhlakul karimah especially for businesses , such as dishonesty in trade practices ; use of hazardous materials which are mixed by a certain type of food , counterfeit products and documents , and various other irregularities without worrying about the values that are actually very essential because humans do everything with responsibility.